Культурная гибридность глазами Андрея Битова: Армения, Россия, Грузия - Elena Chkhaidze (eSamizdat)
This article discusses the presentation of cultural hybridity in the USSR based on Andrei Bitov’s book Imperiia v chetyrekh izmereniiakh [Empire in Four Dimensions]. The third dimension, Kavkazskii plennik [The Prisoner of the Caucasus], is taken as the basis for the analysis and describes the travel to Soviet Armenia and Georgia. The analysis focuses on the intertwining of central and provincial cultures within the Soviet empire and the extent to which this mixing occurs.